Morphological Characteristics of Intestinal Vessels of Animals with an Experimental Model of Diabetes Mellitus Type 2 Complicated by Microangiopathy - Alisher Okhunov1, Rajabbay Israilov1, Shukhrat Razzakov1, Pakiza Azizova1, Alisher Mominov1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Diabetes mellitus and its complications are considered far from unresolved problems of modern medicine.An important aspect in solving fundamental problems is experimental research aimed at assessing the stateof change of pathogenetic important key positions in the development of such a formidable complicationof diabetes as angiopathy. On the other hand, surgeons’ great interest in bariatric and metabolic surgery,as method of surgical treatment of type 2 diabetes mellitus, requires in-depth studies to assess the stateof angiogenic changes in the organs of the gastrointestinal tract, namely in the intestine. The articledescribes the morphological changes in the vascular capillary bed in the dynamics of the development ofa new experimental model of diabetes mellitus, namely the chemical method of diabetic angiopathy. Thedevelopment of an experimental model of diabetic angiopathy showed the staged nature of the changes inthe form of the initial signs of angiopathy, with perivascular infiltration and edema in the form of congestiveplethora in the flesh until the development of vascular hyalinosis, which indicates the irreversibility of theprocesses of pathological transformation. Thus, the results of morphological studies in the dynamics ofmodeling of diabetic angiopathy indicate the development of diabetes mellitus with its complication in theform of microangiopathy.